Enhanced passive safety surveillance of high-dose and standard-dose quadrivalent inactivated split-virion influenza vaccines in Germany and Finland during the 2022/23 influenza season - Marina Amaral de Avila Machado; Sonja Gandhi-Banga; Sophie Gallo; Tathyana Giannotti Cousseau; Reddappa Maniganahally Byrareddy; Markku Nissilä; Jörg Schelling; Celine Monfredo (Human Vaccines & Immunotherapeutics)
Enhanced Passive Safety Surveillance (EPSS) was conducted for quadrivalent inactivated split-virion influenza vaccines (IIV4) in Germany (high dose [HD]) and Finland (standard dose [SD]) for the northern hemisphere (NH) 2022/23 influenza season. The primary objective was to assess adverse events following immunization (AEFI) occurring ≤7 days post-vaccination. In each country, the EPSS was conducted at the beginning of the NH influenza season. Exposure information was documented using vaccination cards (VC), and AEFI were reported via an electronic data collection system or telephone. AEFI were assessed by seriousness and age group (Finland only). The vaccinee reporting rate (RR) was calculated as the number of vaccinees reporting ≥ 1 AEFI divided by the total vaccinees. In Germany, among 1041 vaccinees, there were 31 AEFI (ten vaccinees) during follow-up, including one serious AEFI. Of 16 AEFI (six vaccinees) with reported time of onset, 15 occurred ≤7 days post-vaccination (RR 0.58%, 95% confidence interval [CI] 0.21, 1.25), which was lower than the 2021/22 season (RR 1.88%, 95% CI: 1.10, 3.00). In Finland, among 1001 vaccinees, there were 142 AEFI (51 vaccinees) during follow-up, none of which were serious. Of 133 AEFI (48 vaccinees) with time of onset reported, all occurred ≤7 days post-vaccination (RR 4.80%, 95% CI: 3.56, 6.31), which was similar to the 2021/22 season (RR 4.90%, 95% CI: 3.65, 6.43). The EPSS for HD-IIV4 and for SD-IIV4 in the 2022/23 influenza season did not suggest any clinically relevant changes in safety beyond what is known/expected for IIV4s.